Pituitary Adenoma Surgery: Retrospective Analysis of My Personal Experience - Shrestha, Prabin; Rajbhandari, Anjana (Nepal Journal of Neuroscience, 2016)
Pituitary tumors are one of the common brain tumors after gliomas, meningieomas and acoustic schwaanomas. It is commonly encountered in Nepal also as in other countries. Retrospective case series analytical study was done. The cases of pituitary adenoma from 2009 till 2015 were included. Types of pituitary adenoma, surgical technique, postoperative morbidities, mortalities and outcome were analyzed. Total 21 cases of pituitary adenoma were operated. All the cases were diagnosed by MRI, plain and contrast. In addition, thorough hormonal evaluation was done. All the cases were operated via transnasal transsphenoidal (TSS) approach. Microscope was used in all the cases whereas endoscope was used in selected cases. Preoperative lumbar puncture and CSF drain was not done in any case. Postoperative transient nasal CSF leak and diabetes insipidus were the most common surgery related morbidities in almost 50% cases which were totally cured with time. All the patients became asymptomatic and got better after surgery. Postoperative mortality and long term morbidity were nil. Recurrence was noted in one case after 3 years of surgery. Pituitary tumor surgery is safe and rewarding provided it is done carefully with skilled hands. TSS is a good approach with minimal postoperative complications. Better to have both microscope and endoscope for TSS. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page:63-67